Analysis of Construction Workers' Perceptions of Company Services (Case Study: PT. Konawe Multi Usaha) - Bachmid, Sitti Nurkhalisah; Lakawa, Irwan; Sufrianto, Sufrianto; Sudardjat, Catrin (Universitas Sulawesi Tenggara, 2022)
In supporting the success of infrastructure development, it is necessary to have good cooperation between owners, contractors and workers which must be supported by the implementation of a project management system. A construction project is a series of activities which are generally short-term, dynamic, with varying intensity of activities and limited funds. If the project construction implementation is not managed properly, it will become a conflict or dispute between the elements involved in project implementation. In the current reform era, improving the quality of public services is a demand for workers where workers have begun to understand their rights as workers/employees. The purpose of the study was to determine the contractor's performance and to determine the perception of construction workers on the services of the company PT. Konawe Multi Usaha. The results showed that the perception of construction workers on the company's services at the company PT. Konawe Multi Usaha is rated by workers in the category of Fairly Good. There are factors that influence the perception of construction workers' satisfaction on company service satisfaction by using the Customer Satisfaction Index (CSI) analysis, the value of worker satisfaction is 73.43%, which means that the level of worker satisfaction is in the Satisfied category